Forced Feeding: New Legal Issues in the Biotechnology Policy Debate - Neil D. Hamilton (Washington University Journal of Law & Policy, 2005)
In the fall of 2000, I presented a paper, Legal Issues Shaping Society’s Acceptance of Biotechnology and Genetically Modified Organisms, at the American Agricultural Law Association annual meeting in St. Louis. The paper inventoried the legal and policy issues shaping America’s approach toward biotechnology and was designed to serve as a tool for understanding the ongoing debate. Thirty months have passed and the pace of consideration of issues relating to society’s acceptance of biotechnology has not slowed. Just as the article was being finished, the StarLink fiasco was beginning. That episode alone has provided the grist for numerous lawsuits and other policy debates. In the intervening thirty months, several issues have become more settled. What follows is an effort both to update many of the issues discussed in the previous article and to make the analysis more timely and complete. In doing so, the Essay will share whatever insights and observations are possible concerning the role that biotechnology will play in our food and agriculture system and how policy and law will be asked to shape that future.
Keywords: Genetically modified foods